Knowledge and Practices of Postnatal Mothers Regarding Newborn Care in a Selected Hospital in West Bengal - Dipa Ghosh; Subhra Rani Das (International Journal of Midwifery Nursing And Practices, 2023)
The health of newborns is significantly impacted by the extent of knowledge and behaviors exhibited by mothers in the postnatal period. By assessing the level of knowledge and practices it is possible to predict the cause and reduce the rate of neonatal mortality and morbidity. A research investigation aimed at evaluating the understanding and routines of postnatal mothers regarding the care of newborns in a chosen hospital located in West Bengal. Quantitative research approach was undertaken. Institutional permission was taken. The sample was collected according to purposive non probability sampling technique from 50 hospitalized postnatal mothers, who were admitted in Postnatal Ward of Ghatal S.D. & S.S. Hospital, Ghatal, Paschim Medinipur, West Bengal. Data were collected as per designated inclusion and exclusion criteria within a week through structured interview schedule and observation. Tool- I was for demographic variables. Tool- II has two parts, Part-A to assess the knowledge level and Part-B to assess the practice level of postnatal mother regarding newborn care. The findings of this study revealed that there were gaps in knowledge and practices of newborn care because of majority of mothers were primi gravida (60%) and type of delivery was LUCS(58%). The present study result revealed that postnatal mothers had adequate knowledge (78%) regarding newborn care but the practices level were moderate (82%). This study concluded that newborn care is important which help to reduce newborn complications and we should aware the mothers about it. So, health education on essential newborn care should be integrated into routine antenatal services which help to improve newborn care practices. The other most important cause of this gapping in now-a-days is the prevalence of corona virus pandemic situation. A comparative study can be done to assess the knowledge and practices level regarding newborn care among rural and urban mothers.
Keywords: knowledge and practices regarding newborn care; postnatal mothers